Analisis Efektivitas Pemeriksaan Akuntansi Terhadap Pengendalian Internal Akuntansi - Irna Susilawati; Kasmanto Miharja; Indriyani Diwantari; Lutfia Putri Salsabila (Pusat Riset dan Inovasi Nasional, 2024)
Accounting audit is an important process in ensuring the integrity and accuracy of a company's financial reports. However, the effectiveness of accounting audits does not only depend on the auditor's ability to find errors or fraud, but also on the company's own internal controls. This research aims to analyze the extent to which the effectiveness of accounting audits depends on the quality of the company's internal control. The research method used is qualitative analysis of historical data The results of the analysis show that the quality of internal control has a direct impact on the effectiveness of accounting audits. Companies with strong internal controls tend to have more effective accounting audits, because auditors can rely on those internal controls in identifying risks and evaluating the reliability of financial data. However, challenges arise when a company's internal controls are inadequate or not implemented consistently. This can result in auditors having to do more detective work and increase the risk of failure to detect errors or fraud. Therefore, companies need to pay attention to improving and improving their internal controls to support the effectiveness of accounting audits. This research provides important insights for company management and auditors in understanding the complex relationship between internal control and the effectiveness of accounting audits. By strengthening internal controls, companies can improve the quality of their financial reporting and reduce potential risks associated with errors or fraud.